OUTCOMES OF LASER HEMORRHOIDOPLASTY IN THE TREATMENT OF SYMPTOMATIC HEMORRHOIDS AT SAIDU GROUP OF TEACHING HOSPITAL (The Research of Medical Science Review, 2024)
Purpose of study: Common surgical approaches to the management of hemorrhoid disease such as hemorrhoidectomies are with severe postoperative pain and it takes prolong recovery time. Our study is aimed to perform laser hemorrhoidoplasty (LHP) in patients with symptomatic hemorrhoid disease that did not respond to conservative management in population of Malakand division Pakistan. Methods: In our study 60 patients with 3rd and 4th degree hemorrhoids were prospectively included for LHP. Outcomes such as Postoperative pain, early return to work, and quality of life were compared with standard Milligan-Morgan hemorrhoidectomy and follow up was done at 7th day, 1 month and 6 months.Results: The LHP group had significantly lower mean predicted pain scores on days 1 and 2 and lower defecation pain scores and lower analgesia use on days 1 and 2 and followed up visits. Out of 60 patients 61.7% patient have no pain while 35% patient had mild pain which relieved with paracetamol and while negligible number of patient (1.7%) have moderate to severe pain. The median time to return to normal function was significantly lower in the LHP group (2 days vs. 9 days for open hemorrhoidectomy). Similarly, the median days to return to the workplace was significantly lower in the LHP group (3 days vs. 13 days for open hemorrhoidectomy). During follow-up (6 months), symptoms of the patient and all Quality of life were improved significantly, among those with 3rd and 4th degree hemorrhoidal disease. Conclusion: This study demonstrates decreased pain scores, early return to work and better quality of life with this innovative procedure in the population of Malakand division which indicates that laser hemorrhoidoplasty can be used as better alternative of standard Mulligan Morgan hemorrhoidectomy.